2020
DOI: 10.1002/jcsm.12574
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in malnourished older adults diagnosed by ESPEN and GLIM criteria in the SarcoPhAge study

Abstract: Background The Global Leadership Initiative on Malnutrition (GLIM) criteria have been recently launched by consensus of the major nutrition societies. GLIM criteria are partly constructed on the previous definition of malnutrition developed by the European Society of Clinical Nutrition and Metabolism (ESPEN). We aimed to assess malnutrition according to the ESPEN and GLIM criteria at baseline and to determine the corresponding risk of mortality during a 4-year follow-up in community-dwelling older adults from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 52 publications
(125 reference statements)
1
63
1
Order By: Relevance
“…The study was conducted in Belgium and included 534 older volunteers at baseline, which were annually followed-up from June 2013 to September 2019. A complete protocol of the SarcoPhAge study is available [1,27,28].…”
Section: Populationmentioning
confidence: 99%
“…The study was conducted in Belgium and included 534 older volunteers at baseline, which were annually followed-up from June 2013 to September 2019. A complete protocol of the SarcoPhAge study is available [1,27,28].…”
Section: Populationmentioning
confidence: 99%
“…The presence of GLIM-DCM has been reported to be associated with higher mortality rates in communitydwelling older adults. 25 The inclusion of GLIM-DCM in the Comprehensive Geriatric Assessment may help prevent or improve poor outcomes in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The Global Leadership Initiative on Malnutrition (GLIM) criteria provided the first consensus-based universal definition of malnutrition suitable for adults in every healthcare setting [ 7 ]. Several studies have reported malnutrition prevalence as evaluated by the GLIM criteria and explored the adverse effects in a community setting [ 8 , 9 ]. Sanchez-Rodriguez et al reported that 23.4% of community-dwelling older individuals in Belgium were malnourished, according to the GLIM criteria [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported malnutrition prevalence as evaluated by the GLIM criteria and explored the adverse effects in a community setting [ 8 , 9 ]. Sanchez-Rodriguez et al reported that 23.4% of community-dwelling older individuals in Belgium were malnourished, according to the GLIM criteria [ 8 ]. In addition, malnourished older individuals had a 4.4-fold higher mortality risk [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation